IMPLEMENTASI KINERJA UU NO 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK PELAYANAN INFORMASI DAN KOMUNIKASI - prima degodona; Riana Lumban Raja; Thendrik Juniadi Buulolo (LPPM Universitas HKBP Nommensen, 2021)
This study aims to explore public information services for the community. The method used is qualitative. Research data obtained through interviews, observations, and documentation. Informants of this research, the Head of the Office of Communication and Information Technology, employees and the public. The results showed that public information disclosure at the Toba Regency Communications and Informatics Service still lacks communication in cooperation, especially OPD, is still classified as very relaxed in providing the latest news for employees who work in the information sector, and journalists are concerned with personal interests, so that the government in despise society. In terms of resources, especially the Diskominfo facilities, it is still very lacking, as well as the staff / staff who are experts in the program field, so the staff is very lacking in providing important information to the public, in terms of the bureaucratic structure, Diskominfo has provided supervision and implementation of the Act. Public Information Disclosure has at least been accepted by the people of Toba Regency, and in terms of the disposition of the Toba Regency Communication and Information Office, it has tried well to respond to all the complaints experienced by its people because it is the main priority of Diskominfo in providing openness to the community.